Past, Present and Future of a Habitable Earth The Development Strategy of Earth Science 2021 to 2030 (SpringerBriefs in Earth System Sciences, 2022)
This perspective of this book views Earth's various layers as a whole system, and tries to understand how to achieve harmony and sustainable development between human society and nature, with the theme of " habitability of the Earth." This book is one effort at providing an overview of some of the recent exciting advances Chinese geoscientists have made. It is the concerted team effort of a group of researchers from diverse backgrounds to generalize their vision for Earth science in the next 10 years. The book is intended for scholars, administrators of the Science and Technology policy department, and science research funding agencies. This is an open access book.